Does social security need saving? Providing for retirees throughout the twenty-first century - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 1999)
Projections of an impending crisis in financing Social Security depend on unduly pessimistic assumptions about basic demographic and economic variables. Moreover, even if the assumptions are accepted, the projected gap between Social Security revenues and expenditures would not constitute a crisis and could be eliminated with relatively simple adjustments when it occurs. The real issue regarding our ability to provide for retirees throughout the coming century is not the size of Social Security Trust Funds, but the size and distribution of the whole economic pie. When the issue is viewed in this light, it becomes clear that most proposals to save the system - locking away budget surpluses, investing the Trust Funds in the stock market, privatization, reduction of benefits - do not address the real problem of caring for future retirees. Solutions consistent with the true nature and scope of the problem lie not within the Social Security system itself but in the realm of a general fiscal policy aimed at ensuring the growth of the economy.
Keywords: 330